Recurrent or recidivant biliary ileum. - Matteucci, Pablo; Lerena, Ana; Malán, Enzo (Cirugía del Uruguay, 1984)
Upon observation of two cases of recurrent biliary ileum the author analyses clinical and pathological aspects of this affection. Prophylaxis is considered and the advantages and inconvenient of simultaneous surgical treatment of the ileum and the biliary focus.